IoT Based Nozzle Actuation System Design for Automated Fish Feed Distribution - Sentot Novianto; Larasati Putri; Amrullah Ibrahim; Tono Sukarnoto; Faisal Adinegoro; Supriyadi Supriyadi; Nanang Ruhiyat (Faculty of Science and Technology, Universitas Sanata Dharma, 2026)
This study presents the design and development of an IoT-based nozzle actuator system intended to improve the accuracy and efficiency of automatic fish-feed distribution. The system was designed using an ESP32 microcontroller as the central controller, a servo motor as the nozzle-direction actuator, and the Blynk application as the remote monitoring and control interface. This configuration enables users to adjust the nozzle’s direction and feed-dispersion intensity through both manual control and scheduled timer modes. A series of experiments was conducted to evaluate mechanical performance, IoT connectivity stability, response time, and cross-device application compatibility. The experimental results indicate that the proposed system improves feed-distribution efficiency by 32.6% compared to conventional manual methods. Feed waste was reduced by 28.4% due to more uniform distribution and minimized overfeeding. The average command-to-actuator response time was measured at 0.82 seconds, demonstrating stable real-time performance. Application testing across five smartphone devices (Redmi 12, Huawei P30, Redmi Note 9, Samsung M23, and Little M3) achieved a 100% success rate for login, timer functions, and manual ON commands, confirming the reliability of the IoT control interface across multiple platforms. Compared with traditional automatic feeders, the developed prototype offers more precise nozzle orientation, flexible remote operation, and an adaptive feed-dispersion pattern. The integration of actuation mechanisms with IoT-based control provides a smarter and more efficient automation solution suitable for small- to medium-scale aquaculture systems. Overall, the findings demonstrate that the proposed design delivers superior distribution performance and operational flexibility, representing a meaningful advancement over existing feeding technologies.